Paritaprevir as a pan-antiviral against different flaviviruses - Yadav, R. P.; Jena, N. R. (Frontiers in Molecular Biosciences, 2025)
IntroductionThe flavivirus infections caused by the Zika virus (ZIKV), Dengue virus (DENV), and West Nile virus (WNV) cause mild to serious pathological conditions, such as fever, joint pain, shock, internal bleeding, organ failure, nausea, breathlessness, brain tissue damage, neurodegenerative diseases, and deaths. As currently no efficient vaccine or drug is available to prevent or treat these diseases in humans, it is essential to identify potential drug-like molecules to treat these diseases. For these reasons, several known anti-viral drugs are repurposed against the proteases of ZIKV, WNV, and DENV to inhibit their activities.MethodsThe GOLD 5.0 molecular docking program was used to dock 20 HIV and HCV drugs against the ZIKV protease. Based on docking scores, 5 drugs were found to bind to the ZIKV protease with high affinities. Subsequently, the AMBER ff14SB force field was employed to simulate these drug-bound complexes of ZIKV protease. The MM/PBSA free energy method was utilized to compute the binding free energies of these complexes. Consequently, the two best ZIKV protease inhibitors were repurposed against the proteases of DENV and WNV.Results and DiscussionIt is found that out of the 5 drugs, Ritonavir and Paritaprevir bind to the NS2B-NS3 protease of the ZIKV strongly with the Gibbs binding free energies (∆Gbind) of −17.44±3.18 kcal/mol and −14.25±3.11 kcal/mol respectively. Remarkably, Ritonavir binds to the ZIKV Protease about 12 kcal/mol more strongly compared to its binding to the HIV protease. It is further found that Paritaprevir binds to DENV and WNV proteases as strongly as it binds to the ZIKV protease. Hence it is proposed that Paritaprevir may act as a potent pan-antiviral against the Zika, West Nile, and Dengue viral diseases.